Anticipated Stigma from Family and Loneliness Among Chinese Gay Men: The Mediating Role of Guilt and the Moderating Role of Self-Compassion - Yang Yang; Wu Yifei; Cao Jun; Hou Liang; Gao Chen (American Journal of Men's Health)
In China, men are responsible for continuing the family line and the primary source of pressure for adult Chinese gay men comes from the expectations and demands of patrilineal nuclear families in general, parents in particular, and pressure to comply with social sexual orientation and identity norms and to perpetuate the family. Previous studies on the loneliness of LGBT individuals have paid less attention to the loneliness of gay men from a Chinese cultural perspective. This study investigated the relationship between anticipated stigma from family and loneliness among gay men. A sample of 408 gay men in China was recruited to investigate the associations between anticipated stigma from family, loneliness, guilt, and self-compassion using the 6-item University of California Los Angeles Loneliness Scale, the Anticipated Stigma Questionnaire, the Chinese version of the Guilt Inventory, and the Chinese version of the Self-Compassion Scale. The results showed that gay men’s anticipated stigma from family was positively associated with loneliness, guilt mediated the relationship between anticipated stigma from family and loneliness, and the isolation dimension of self-compassion moderated the relationship between anticipated stigma from family and guilt. The presence of high self-compassion mitigated the positive association between anticipated stigma from family and guilt.